2010
DOI: 10.2174/1874943701003010158
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Shopping Systems for Blind and Visually Impaired Individuals: Design Requirements and the State of the Art

Abstract: Independent grocery shopping is one of the most functionally challenging tasks for visually impaired and blind individuals. Many assistive shopping systems have been developed to address the problem of blind grocery shopping. In this article, we identify several design requirements for assistive shopping systems and analyze existing approaches to see how well they meet them. Our objective is to shed some light on possible research and development directions for the accessible blind shopping community and to of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Researchers at Utah State University offer a comprehensive analysis of design requirements for mobile assistive technologies to assist visually-impaired shoppers and identify the main activities underpinning conventional shopping behavior as product selection and browsing before purchasing, navigating within a store, and searching for and identifying actual products 55 . On the basis of their analysis, they developed ShopTalk 74 to assist visuallyimpaired shoppers to navigate through a store and locate target products by scanning barcodes both on shelves and on individual products.…”
Section: Independent Shoppingmentioning
confidence: 99%
“…Researchers at Utah State University offer a comprehensive analysis of design requirements for mobile assistive technologies to assist visually-impaired shoppers and identify the main activities underpinning conventional shopping behavior as product selection and browsing before purchasing, navigating within a store, and searching for and identifying actual products 55 . On the basis of their analysis, they developed ShopTalk 74 to assist visuallyimpaired shoppers to navigate through a store and locate target products by scanning barcodes both on shelves and on individual products.…”
Section: Independent Shoppingmentioning
confidence: 99%
“…Thus, speech may become a viable option for controlling eyes-free information browsing. One caveat, however, is that, even if speech recognition becomes completely accurate, some people may still have privacy reservations of speaking commands to the system in public spaces [12].…”
Section: Discussionmentioning
confidence: 99%
“…r Several systems for shopping are available to assist VI people; however, blind buyers show less interest to buy those devices in addition to the devices that they are already familiar with (Kulyukin & Kutiyanawala, 2010 r Cooperation between teachers and students is important to suit the individual neeeds of a VI student when using e-accessibility (Carrière, 2012).…”
Section: E-accessibilitymentioning
confidence: 99%
“…However, radios, voice recorders, CDs and talking books are less costly solutions for e-accessibility (Bonnah, Nkansah, & Unwin, 2010). Kulyukin and Kutiyanawala (2010) found that even though some devices assist VI people in relation to instore navigation and product shopping, none of these meet all requirements. Further, VI people are less interested in buying newer technology to replace devices they are already using.…”
mentioning
confidence: 99%